The role of defense cuts in the California recession: computable general equilibrium models and interstate factor mobility - Hoffman, S.; Robinson, Sherman; Subramanian, Shankar (Wiley, 1996)
ABSTRACT.This study develops a computable general equilibrium (CGE) model of California to examine the impact of recent defense cuts on the state's economy. The study demonstrates use of a CGE model to examine the sensitivity of regional economy models to assumptions about factor migration. Model variants include input‐output and closed economy models as limiting cases. The results show that the California economy is sensitive to defense cuts. The multiplier relating the impact of defense cuts to state product ranges from one to almost five, depending on the degree of interstate factor mobility.